Non-nasal, atypical retinochoroidal coloboma in pediatric patients: Case series and review - Serena Shah; Natasha Ferreira Santos da Cruz; Patrick Staropoli; Francisco Lopez-Font; Ta Chen Peter Chang; Audina Berrocal (American Journal of Ophthalmology Case Reports, 2024)
Purpose: To report 2 cases of atypically located, non-nasal colobomas in the pediatric population. Observations: A 3-week-old female neonate with no known past ocular or medical history was diagnosed with temporal iris and chorioretinal coloboma with tractional membranes upon examination under anesthesia and imaging. A 9-year-old female with a history of bilateral sensorineural hearing loss and left mild hydronephrosis presented with a temporal chorioretinal coloboma associated with retinal detachment. Conclusions and importance: Very few cases of atypically located, non-nasal pediatric colobomas have been reported, and they lack a clear cause or mechanism of formation. Continued documentation of their occurrence and research into their formation at a molecular and embryological level are warranted to better understand their pathogenesis.